Consensus guidelines for the treatment of yeast infections in the haematology, oncology and intensive care setting, 2014. Issue 12 (December 2014) - Chen, S. C.; Sorrell, T. C.; Chang, C. C.; Paige, E. K.; Bryant, P. A.; Slavin, M. A.
Abstract Pathogenic yeast forms are commonly associated with invasive fungal disease in the immunocompromised host, including patients with haematological malignancies and patients of haemopoietic stem cell transplants. Yeasts include the Candida spp., Cryptococcus spp., Pneumocystis jirovecii and some lesser‐known pathogens. Candida species remain the most common cause of invasive yeast infections (and the most common human pathogenic fungi). These guidelines present evidence‐based recommendations for the antifungal management of established, invasive yeast infections in adult and paediatric patients in the haematology/oncology setting. Consideration is also given to the critically ill patient in intensive care units, including the neonatal intensive care unit. Evidence for 'pre‐emptive' or 'diagnostic‐driven antifungal therapy' is also discussed. For the purposes of this paper, invasive yeast diseases are categorised under the headings of invasive candidiasis, cryptococcosis and uncommon yeast infections. Specific recommendations for the management of Pneumocystis jirovecii are presented in an accompanying article (see consensus guidelines by Cooley et al. appearing elsewhere in this supplement).